2006
DOI: 10.1007/s11892-006-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic aspects of islet cell transplantation

Abstract: Percutaneous transhepatic intraportal pancreatic islet transplantation is an experimental treatment for patients with type 1 diabetes. The radiologic aspects of pancreatic islet transplantatinn are described, including a review of interventional radiology, ultrasound, and fluoroscopy image-guided, minimally invasive techniques and procedure-related complications and their avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Patients with known thrombophilia (protein C, S, anti-thrombin III, factor V Leiden deficiency) should not undergo percutaneous intraportal islet transplantation [87]. After brief skin infiltration with local anesthesia, and with ultrasonic guidance, a 22-gauge Chiba needle is advanced intraparenchymally until a peripheral branch of the right portal tree is identified [88][89][90][91][92][93]. An 18-gauge guidewire is then threaded in to the main portal vein and exchanged for a 4-5 French angio catheter (e.g.…”
Section: Intraportal Accessmentioning
confidence: 99%
“…Patients with known thrombophilia (protein C, S, anti-thrombin III, factor V Leiden deficiency) should not undergo percutaneous intraportal islet transplantation [87]. After brief skin infiltration with local anesthesia, and with ultrasonic guidance, a 22-gauge Chiba needle is advanced intraparenchymally until a peripheral branch of the right portal tree is identified [88][89][90][91][92][93]. An 18-gauge guidewire is then threaded in to the main portal vein and exchanged for a 4-5 French angio catheter (e.g.…”
Section: Intraportal Accessmentioning
confidence: 99%
“…Currently, the preferred transplantation site is the portal vein of the liver, which is not optimal due to venous hypoxemia and the potential risk of thrombosis. [95] Islet transplantation in the subcutaneous site would be more accessible and minimally invasive; however, the lack of early vascularization of the graft may result in loss of function and inability to restore normoglycemia due to poor graft oxygen supply. [96] [9799]…”
Section: Mscs and T1dmentioning
confidence: 99%
“…54 Reports have suggested 35 U/kg heparin if packed cell volume is <5 mL and 70 U/kg heparin if packed cell volume >5 mL. [55][56][57] On average, approximately 300,000 islet cells are obtained from purification of a single pancreas. 58 Compared with whole organ pancreas transplants, which require one donor per recipient, purification of enough islet cells for a single infusion typically requires two donors.…”
Section: Islet Cell Preparationmentioning
confidence: 99%
“…It can be diagnosed with ultrasound or contrast-enhanced CT scan, which may reveal filling defects in the portal veins and sequelae such as diffuse small bowel thickening. 55 A large prospective study performed by Kawahara et al found that portal vein thrombosis is preventable as long as therapeutic anticoagulation is started in the interventional radiology suite and maintained in the postprocedural setting (for at least 10 days) and packed cell volume is limited to less than 5 mL. 55,57 Treatment for portal vein thrombus is usually with systemic anticoagulation.…”
Section: Complicationsmentioning
confidence: 99%